Corbin's concepts of fitness and wellness a comprehensive lifestyle approach - Welk, Gregory J.; Welk, Greg; Corbin, William R.; Welk, Karen A.
"This edition of Concepts of Fitness and Wellness has been thoroughly updated with new elements aimed at enhancing student learning. Readers will find an even stronger focus on personal responsibility and self-management skills as these are critical for adopting and sustaining healthy lifestyles. Each Concept begins with Learning Objectives and a new element Why It Matters! to introduce key themes that help students see the direct relevance of the material. Each Concept ends with a new section Using Self-Management Skills to help the reader apply the information to everyday life. Updated descriptions in the Strategies for Action section then introduce the specific lab activities that provide opportunities to practice and learn these self-management skills. The educational features in each Concept have also been completely updated, with new links and questions available in Connect to promote personal exploration of the content. A variety of video vignettes are embedded within the eBook and linked to Connect activities to help explain complex issues and provide opportunities for personal reflection and critical thinking"--Provided by publisher.
CAC Camia (Recommending faculty) AY2022-2023
Includes bibliographical references (pages 506-510) and index.
Keywords: Physical fitness; Exercise; Health